Risk Management of Toxic Hazardous Substances To Improve Occupational Safety And Health Uptd Dlh Purwakarta Regency - Widiya (Inaba of Community Services Journal, 2023)
The purpose of qualitative research is to determine the implementation of risk management and K3 in B3 waste management at UPTD Environmental Laboratory DLH Purwakarta Regency. The source of this research data was obtained from the results of in-depth interviews with the main informant and supporting informants. Using SWOT research analysis (Strength, Weakness, Opportunity, threat) to show that risk management has been implemented thoroughly based on implementation in carrying out services documented in SOPs and Monitoring which is carried out every three months. The application of K3 is in accordance with Permen-LHK No. 23 of 2020 concerning Environmental Laboratories. Obstacles in B3 waste management are inappropriate waste management due to lack of knowledge and certification competition owned by B3 waste managers. Therefore, a B3 waste management strategy was made with a SWOT analysis in the form of providing an education and training budget to obtain B3 waste management competency certification.